PREVALENCE OF STRESS, ANXIETY, DEPRESSION AND ASSOCIATED FACTORS IN MEDICAL STUDENTS: A REVIEW AND ANALYSIS (Vietnam Journal of Community Medicine, 2026)
Background: Depression constitutes a significant public-health burden worldwide, particularly among university students.Objective: This study aimed to synthesize existing evidence on the prevalence of stress, anxiety, and depression among medical and pharmaceutical students in Vietnam and to identify associated factors through a literature review.Methods: A total of 11 studies published up to July 2022 were retrieved from Google Scholar. The reviewed studies employed validated instruments, including the PHQ-9, DASS-21, and CES-D scales, to assess stress, anxiety, and depression either independently or in combination. The internal consistency and reliability of these instruments were evaluated using Cronbach’s alpha coefficients.Results: The findings demonstrated wide variability in prevalence estimates, largely attributable to differences in measurement scales and study designs.Conclusion: The use of at least two standardized measurement instruments is recommended to enhance diagnostic accuracy and facilitate comparison across studies.
Keywords: stress, anxiety, depression, measurement scales, medical students, pharmaceutical students